MENATA ULANG PEMILUKADA MENUJU TATA KELOLA PEMERINTAHAN DAERAH DEMOKRATIS, AKUNTABEL, DAN BERKELANJUTAN - Dewi, Kurniawati Hastuti (Jurnal Penelitian Politik, 2015)
This research formulated a better model of direct local elections for Indonesia. Based on the depth findings of three series of researches (2012, 2013, 2014) on direct local elections under Law No. 32/2004, this research recommended the â€œasymmetricalâ€ direct local elections model in which direct local elections shall be varied in level depends on the quality of human development index and regional budget capacity. This research also suggested regulative and technical interventions to achieve democratic, accountable and sustainable direct local elections.Keywords: direct local elections, assymmetrical, local government.